Розвиток індустрії 4.0 та її значення для міжнародної торгівлі - Авксентьєв, Євген Олександрович; Avksentiev, Yevhen (ЦНТУ, 2024)
У роботі узагальнено сутнісні характеристики поняття «Індустрія 4.0» та виділити основні етапи її еволюції. Систематизовано теоретичні підходи до визначення впливу Індустрії 4.0 на продуктивність та економічне зростання країн. Проаналізовано теоретичні засади формування факторів впливу Індустрії 4.0 на міжнародну торгівлю в умовах глобальних викликів. Визначено основні тенденції розвитку міжнародної торгівлі під впливом Індустрії 4.0. Проаналізовано структурні зміни міжнародної торгівлі під впливом чинників Індустрії 4.0. Визначено вплив Індустрії 4.0 на конкурентоспроможність країн. Охарактеризовано особливості зовнішньої торгівлі України з урахуванням факторів Індустрії 4.0. Визначено напрями удосконалення міжнародної конкурентної стратегії України на основі використання переваг Індустрії 4.0. The thesis summarizes the essential characteristics of the concept of "Industry 4.0" and highlights the main stages of its evolution. Theoretical approaches to determining the impact of Industry 4.0 on the productivity and economic growth of countries are systematized. The theoretical foundations of the formation of factors influencing Industry 4.0 on international trade in the conditions of global challenges are analyzed. The main trends in the development of international trade under the influence of Industry 4.0 have been determined. Structural changes in international trade under the influence of Industry 4.0 factors are analyzed. The influence of Industry 4.0 on the competitiveness of countries is determined. The features of Ukraine's foreign trade are characterized, taking into account the factors of Industry 4.0. The areas of improvement of the international competitive strategy of Ukraine based on the use of the advantages of Industry 4.0 have been determined.
Development of Industry 4.0 and its Significance for International Trade
Keywords: четверта промислова революція; міжнародна торгівля; технологічний розвиток; міжнародна конкурентоспроможність; the fourth industrial revolution; international trade; technological development; international competitiveness